Online responses to the ending of the one-child policy in China: implications for preconception care. (1st October 2016) - Liu, Fuqin; Bao, Jiaming; Boutain, Doris; Straughn, Marcia; Adeniran, Olusola; DeGrande, Heather; Harrell, Stevan
Abstract: Aim: A critical analysis of online public postings in response to the news about the ending of China's one-child policy was conducted. The specific study aims were to 1) identify the dominant public discourse in response to the news about the ending of the one-child policy and the beginning of the new two-child policy, and 2) explore implications for preconception care from the public discourse. Material and methods: Data sources were 10 top-ranked, online news media sites in China, including one Hong Kong-based media site. Selected online sites announced the news about the ending of the one-child policy on 29 October 2015. Online postings associated with the first news release of each online media site before midnight of 29 October were collected and analyzed. Critical discourse analysis was used for data analysis. Results: Three main discourse concepts were identified. The online postings referenced the concepts of cost, generation, and timing with regard to the ending of the one-child policy and the beginning of the new two-child policy. Each concept represents an aspect of the public's view of preconception care, particularly interconception care, in China. Discussion: These findings suggest that the change in the family planning policy may not result in a huge surge in the population in a short period of time, as some may opt not to have a second child. Nonetheless, there is an urgent need to incorporate interconception care into various health initiatives, as it is a time-sensitive choice for many couples to have a second child.